Development and structural characterization of chitosan ﬁlms containing Eucalyptus globulus essential oil: Potential as an antimicrobial carrier for packaging of sliced sausage. (September 2018) - Azadbakht, Ehsan; Maghsoudlou, Yahya; Khomiri, Morteza; Kashiri, Mahboobeh
Highlights: Eucalyptus globulus essential (EGO) in vapour phase has great potential in inhibit bacterial growth. Physical properties of chitosan film can be enhanced by incorporating with EGO. Chitosan as a carrier of EGO improved antimicrobial properties of the films in liquid medium. Vapor phase inhibition of chitosan film containing EGO against bacterial growth was so weak. Chitosan films containing EGO have potential as an antimicrobial carrier for inhibiting bacterial growth in packaging of sliced sausage. Abstract: Novel antimicrobial biopolymer ﬁlms based on the incorporation Eucalyptus globulus essential oil (EGO) in chitosan were successfully developed and characterized as an active film for packaging of sliced sausage. Characterization of the ﬁlms revealed that incorporation of EGO (0.5, 1.5, and 1.5%) in the biopolymer led to change in morphology, mechanical and barrier properties. Antibacterial activity of EGO was assayed against Salmonella entertidis and Escherichia coli as Gram-negative bacteria; furthermore, Bacillus cereus and Staphylococcus aureus as Gram-positive bacteria. Results showed that the EGO was able to generatean excellent antibacterial effect in liquid and vapour phases. Chitosan ﬁlms with 1.5% EGO in liquid medium produced 4.22, 3.98, 4.55, and 4.71 log reduction against S. aureus, E. coli, B. cereus and S. entertidis, respectively. However, only minor population reduction of bacteria was observed in the vapour phase. The highest antibacterial activity in sliced sausage was obtained by chitosan ﬁlms containing 1.5% EGO (1.01 log reduction). This work highlighted that EGO incorporation in chitosan is a promising approach in order to control risk of foodborne contamination in a real food system.